Composite Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma and T-Prolymphocytic Leukemia Presenting with Lymphocytosis, Skin Lesions, and Generalized Lymphadenopathy - Ali Sakhdari; Guilin Tang; Lawrence E. Ginsberg; Cheryl F. Hirsch-Ginsberg; Carlos E. Bueso-Ramos; L. Jeffrey Medeiros; Roberto N. Miranda (Hindawi Limited, 2019)
Chronic lymphocytic leukemia (CLL) is the most common type of leukemia in Western countries with an incidence of 3-5 cases per 100,000 persons. Most patients follow an indolent clinical course with eventual progression and need for therapy. In contrast, T-prolymphocytic leukemia (T-PLL) is a rare type of T-cell leukemia with most patients having an aggressive clinical course and a dismal prognosis. Therapies are limited for T-PLL patients and there is a high relapse rate. Morphologically, the cells of CLL and T-PLL can show overlapping features. Here, we report the case of a 61-year-old man who presented with a clinically indolent CLL and T-PLL, initially diagnosed solely and followed as CLL, despite the presence of an associated but unrecognized aberrant T-cell population in blood. After 2 years, the T-PLL component became more apparent with cutaneous and hematologic manifestations and the diagnosis was confirmed by immunophenotypic and cytogenetic analysis. Fluorescence in situ hybridization demonstrated an ATM deletion in both CLL and T-PLL components. Retrospective testing demonstrated that composite CLL and T-PLL were both present in skin and lymph nodes as well as in blood and bone marrow since initial presentation. This case is also unique because it highlights that a subset of T-PLL patients can present with clinically indolent disease. The concomitant detection of ATM mutation in CLL and T-PLL components raises the possibility of a common pathogenic mechanism.